(untitled) (African Scientific Reports, 2025)
Wastewater from the confectionery industry exhibits marked daily and seasonal variations, complicating its management and disposal. This study investigated the physico-chemical characteristics, heavy metal content, and microbial load of effluents from a confectionery processing plant using American Public Health Association (APHA) standard procedures. At the discharge point, the effluent showed temperature (25.02±0.15 °C), turbidity (1.00 NTU), pH (6.20±0.29), electrical conductivity (2295.00±3.62 µs/cm), total dissolved solids (1708.00±19.70 mg/L), total suspended solids (6252.00±0.30 mg/L), total hardness (CaCO3) (1141.30±0.03 mg/mL), oil and grease (5.60±0.00 mg/L±), dissolved oxygen (4.76±0.02 mg/L), COD (8900±0.00 mg/L), BOD (181.80±0.37 mg/L), free chlorine (0.25 mg/L), phosphate (9.418 mg/L), nitrate (387.60 mg/L). Heavy metals (mg/mL) included Mg (25.71), Zn (<0.0010), Pb (<0.0100), Cu (0.0100), Mg (0.0564), Ni (0.0064), and Cd (<0.0020). The total plate count was (238 cfu /100 mL), while the total coliforms count exceeded 1600 MPN/ 100 mL. Comparison with FEPA and NESREA discharge standards indicated that most parameters met regulatory limits, except TDS, TSS, alkalinity, nitrate, chloride, phosphorus, oil and grease, total coliforms, Fe, BOD, and COD, which exceeded permissible thresholds. The release of such inadequately treated effluents poses environmental and public health risks. Strengthened regulatory enforcement is recommended in industrial zones such as Lagos State, Nigeria.